(untitled) (Revista de História da UEG (REVHIST), 2023)
Resenha da Obra: ARZABE, Cristina; MACIEIRA, Josiane C; MENEZES, Raquel SS; BALIZA, Danielle P; MOURÂO, Tânia F. (Org.). Mulheres dos cafés no Brasil. 1ª ed. Brasília DF: Embrapa, 2017.